KOMUNIKASI KORPORAT DALAM KONTEKS MARGER DAN AKUISISI: STRATEGI DAN DAMPAKNYA - Jumiah, Jumiah; Fitrianti, Rizqi; Susilawati, Eka; Laksana, April (Gapenas Publisher, 2025)
This research is motivated by increasing merger and acquisition (M&A) activity at the global and national levels, where corporate communication has become a critical factor in determining the success of the integration process. Although the value of global M&A transactions will reach US 3.8 trillion by 2022, around 70% of M&A transactions fail to achieve their strategic objectives, with poor communication being one of the main factors of such failure. This research aims to analyze the strategy and impact of corporate communication in the M&A context, with a special focus on effective communication practices at the global level and their adaptation in the Indonesian context using a systematic literature study research method. The research results show that companies that implement a structured communication strategy from the early stages of M&A have a 40% higher integration success rate. In Indonesia, communication approaches that combine global standards with local values, such as deliberation and a family approach, have proven to be more effective in facilitating the integration process. Research also reveals that companies that integrate digital platforms in their M&A communications strategy achieve 45% higher levels of employee engagement, while social media monitoring is becoming increasingly critical with 70% of reputation issues during M&A stemming from discussions on social media. This research provides theoretical contributions to the development of adaptive M&A communication models as well as practical implications for communications professionals and executives involved in the M&A process